Centella asiatica alleviates diabetes‐induced changes in fatty acid profile and oxidative damage in rat testis. (13th July 2020) - Oyenihi, Ayodeji B.; Opperman, Maretha; Alabi, Toyin D.; Mpahleni, Buhle; Masola, Bubuya
Abstract: The in vivo effects of Centella asiatica L. Urban (Family: Apiaceae; CA) on diabetes‐induced testicular fatty acid misdistribution and oxidative injury were investigated. Diabetic rats were treated with vehicle, CA or metformin daily for 14 days by oral gavage. Fatty acid (FA) content in testis was analysed using gas chromatography‐flame ionisation detection while redox indices were measured as peroxide value (PV), malondialdehyde (MDA), oxygen radical antioxidant capacity (ORAC), reduced glutathione (GSH), glutathione S‐transferase (GST) and glutathione peroxidase (GPx) activities. Diabetes increased omega‐6 (61%), and decreased omega‐3 (23%) and monounsaturated fatty acids (MUFA; 18%) compared to non‐diabetic controls. Oxidative injury in diabetic rats was confirmed by increases in PV (112%) and MDA (77%) in addition to decreases in GSH (41%) and activities of GST (19%) & GPx (24%) compared to non‐diabetic controls. CA treatment led to 17% reduction in omega‐6 and 33% rise in MUFA compared to diabetic controls. Additionally, CA ameliorated the oxidative injury and improved antioxidant capacity by increasing GSH (49%), GST (16%) and GPx (23%) when compared to diabetic controls. Data suggest CA potential in alleviating the alterations caused by diabetes in testes through effects on omega‐6 and MUFA; and via increased GSH level and dependent enzyme activities.